2016
DOI: 10.1145/2964791.2901501
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Load Imbalance in Scale-out Data Serving

Abstract: Despite the natural parallelism across lookups, performance of distributed key-value stores is often limited due to load imbalance induced by heavy skew in the popularity distribution of the dataset. To avoid violating service level objectives expressed in terms of tail latency, systems tend to keep server utilization low and organize the data in micro-shards, which in turn provides units of migration and replication for the purpose of load balancing. These techniques reduce the skew, but incur additional moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Prior research characterizing data access patterns in real-world settings has shown that popularity of individual items in a dataset often follows a power-law distribution [5,6,21,37,39,44]. In such a distribution, a small number of hot items receives a disproportionately high share of accesses, while the majority of the dataset observes relatively low access frequency.…”
Section: Motivation 21 Skew and Load Imbalancementioning
confidence: 99%
See 4 more Smart Citations
“…Prior research characterizing data access patterns in real-world settings has shown that popularity of individual items in a dataset often follows a power-law distribution [5,6,21,37,39,44]. In such a distribution, a small number of hot items receives a disproportionately high share of accesses, while the majority of the dataset observes relatively low access frequency.…”
Section: Motivation 21 Skew and Load Imbalancementioning
confidence: 99%
“…An important implication of popularity skew is the resulting load imbalance across the set of servers maintaining the dataset. As shown in Figure 2a, the server(s) responsible for the hottest keys may experience several times more load than an average server storing a slice of the dataset [37]. For instance, Figure 1 shows an example deployment of 128 servers and a data-serving workload with an access skew of α = 0.99.…”
Section: Motivation 21 Skew and Load Imbalancementioning
confidence: 99%
See 3 more Smart Citations